The Topos of an Immured Woman and Failed Attempts at Emancipation: The Case of Emiliya Dvoryanova’s Novel "Земните градини на Богородица" [The Virgin Mary’s Earthly Gardens] - Grażyna Szwat-Gyłybowa (Slavia Meridionalis)
The Topos of an Immured Woman and Failed Attempts at Emancipation: The Case of Emiliya Dvoryanova’s Novel Земните градини на Богородица [The Virgin Mary’s Earthly Gardens]